Glut4 Storage Vesicles without Glut4: Transcriptional Regulation of Insulin-Dependent Vesicular Traffic - Gross, Danielle N. (American Society for Microbiology, 2004)
Two families of transcription factors that play a major role in the development of adipocytes are the CCAAT/enhancer-binding proteins (C/EBPs) and the peroxisome proliferator-activated receptors (PPARs), in particular PPARγ. Ectopic expression of either C/EBPα or PPARγ in NIH 3T3 fibroblasts results in the conversion of these cells to adipocyte-like cells replete with fat droplets. NIH 3T3 cells ectopically expressing C/EBPα (NIH-C/EBPα) differentiate into adipocytes and exhibit insulin-stimulated glucose uptake, whereas NIH 3T3 cells ectopically expressing PPARγ (NIH-PPARγ) differentiate but do not exhibit any insulin-stimulated glucose uptake, nor do they express any C/EBPα. The reason for the lack of insulin-responsive glucose uptake in the NIH-PPARγ cells is their virtual lack of the insulin-responsive glucose transporter, Glut4. The NIH-PPARγ cells express functionally active components of the insulin receptor-signaling pathway (the insulin receptor, IRS-1, phosphatidylinositol 3-kinase, and Akt2) at levels comparable to those in responsive cell lines. They also express components of the insulin-sensitive vesicular transport machinery, namely, VAMP2, syntaxin-4, and IRAP, the last of these being the other marker of insulin-regulated vesicular traffic along with Glut4. Interestingly, the NIH-PPARγ cells show normal insulin-dependent translocation of IRAP and form an insulin-responsive vesicular compartment as assessed by cell surface biotinylation and sucrose velocity gradient analysis, respectively. Moreover, expression of a Glut4-myc construct in the NIH-PPARγ cells results in its insulin-dependent translocation to the plasma membrane as assessed by immunofluorescence and Western blot analysis. Based on these data, we conclude that major role of C/EBPα in the context of the NIH-PPARγ cells is to regulate Glut4 expression. The differentiated cells possess a large insulin-sensitive vesicular compartment with negligible Glut4, and Glut4 translocation can be reconstituted on expression of this transporter.